Quality of worklife and organizational commitment among Malaysian public and government accountants / Mustafa Mohd Hanefah and Ali Yusob Md Zain - Mohd Hanefah, Mustafa; Md Zain, Ali Yusob (Faculty of of Accountancy & Accounting Research Institute (ARI), 2003)
This study was conducted to examine the nature of relationships between the perceived presence of quality of worklife (QWL) factors and organizational commitment using samples from public and government accountants in Malaysia. Accountants from the Big 5 accounting firms and public sector were selected to participate in this study. A QWL measure consisting of seven factors: growth and development, participation, physical environment, supervision, pay and benefit, social relevance, and workplace integration was developed based on Walton's (1974) conception. The three-component model and measure of organizational commitment developed by Allen and Meyer (1990) was adopted in this study. Results of regression analysis indicate that for both groups, only pay and benefit was significant for all dimensions of organizational commitment. In the case of public accountants, two other variables were significant: supervision and social relevant in explaining organizational commitment, and only growth and development and participation were found to be significant among government accountants. Implication and suggestions for further research are also discussed.